Морфологические признаки и экологические особенности Oligodon taeniolatus (Serpentes, Colubridae) - Доценко, И.Б. (Вестник зоологии, 1984)
Detailed data on external morphology and pholidosis with reference to their use in systematics and determination, habits characteristics and results of experimental study in thermal optimum of the snake.